2009
DOI: 10.1017/s1368980008003303
|View full text |Cite
|
Sign up to set email alerts
|

Coffee intake and risk of incident diabetes in Puerto Rican men: results from the Puerto Rico Heart Health Program

Abstract: Objective: To study prospectively the association of coffee intake with incident diabetes in the Puerto Rico Heart Health Program cohort, comprising 9824 middle-aged men (aged 35-79 years). Methods: Of 9824 men, 3869 did not provide a fasting blood sample at baseline, 1095 had prevalent diabetes and 131 were not given fasting glucose tests at any subsequent study visit. Thus, the present analysis includes 4685 participants. Diabetes was ascertained at baseline and at two study visits between 1968 and 1975 usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In many of the prospective analyses conducted, the protective effects of coffee intake have been observed at high levels of consumption (i.e. ≥4 cups/day) [16,[19][20][21][22][23][24]. However, because serving size was a ranked measure in our study, it is difficult to draw conclusions about the level of coffee actually consumed in comparison to other studies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In many of the prospective analyses conducted, the protective effects of coffee intake have been observed at high levels of consumption (i.e. ≥4 cups/day) [16,[19][20][21][22][23][24]. However, because serving size was a ranked measure in our study, it is difficult to draw conclusions about the level of coffee actually consumed in comparison to other studies.…”
Section: Discussionmentioning
confidence: 66%
“…This could have resulted in misclassification of coffee intakes. Other studies have specified a volume of serving size in their dietary questionnaires [4,[16][17][18], which may result in greater accuracy of estimated coffee intake. However, as discussed by van Dam [15], it is difficult to draw conclusions about the protective effect of coffee at a particular level of consumption from the majority of studies due to their use of non-quantified measure of coffee intake and differing definitions of 'cup size' [15].…”
Section: Discussionmentioning
confidence: 99%
“…When dairy intake was presented in servings or times per day, week, or month, we converted the intake to grams per day with the use of standard units of 177 g for total, low-fat, and high-fat dairy; 244 g for total, low-fat, and high-fat milk (585 g for 1 pint of milk); 244 g for yogurt; 43 g for cheese; and 25 g for cream (45,46). When studies reported conversion factors, these factors were applied (14,18,19,28). For several studies (13,15,(19)(20)(21)(22)24) additional data were provided by the authors or coworkers.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The sample size of the cohorts ranged from 640 to 85,884, and the duration of follow-up ranged from 2.6 to 30 y. Nine studies were conducted in the United States (4,14,17,19,21,25,26), 8 in Europe (10-13, 20, 22-24), 3 in Asia (16,27,28), and 2 in Australia (15,18). The dairy foods studied and definitions of dairy categories differed across studies, as described in Supplemental Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Apart from 1 study, which used 24hour dietary recall to obtain an estimate of coffee consumption, 15 panying 95% CIs. With few exceptions, all studies controlled extensively for a range of potential confounders.…”
Section: Measurement Of Exposure and Outcomementioning
confidence: 99%